Peran UD Rumah Adat Minang Selaku Produsen Makanan Ringan Dalam Perlindungan Hukum Terhadap Konsumen (Studi Kasus Di Usaha Dagang Rumah Adat Minang Medan) - Hajijah Juliana Pulungan; Utary Maharani Barus; Zaini Munawair (JUNCTO: Jurnal Ilmiah Hukum, 2019)
Food production activities or processes to be circulated or traded must meet the provisions regarding food sanitation, food additives, contaminated residues, and food packaging. Another thing that should be considered by everyone who produces food is the use of certain methods in food production activities or processes. This research method is library research and field research. Legal arrangements regarding the rights and obligations of business actors and consumers in Indonesia, are in accordance with Law No. 8 of 1999 concerning consumer protection, Law No. 23 of 1992 concerning Health, Law No.18 of 2012 concerning food and the Republic of Indonesia Government Regulation Number 69 of 1999 concerning Food Labels and Advertising The role and responsibilities of the Minang traditional house trade business as a producer. Consumers' legal remedies have been stated in Article 19 of Law No. 8 of 1999 concerning consumer protection. The process of resolution to consumers who complain through compensation with the same chips, by bringing proof of purchase of chips that are no longer suitable for consumption and proof of purchase receipt.